Mengukuhkan Islam Nusantara: Kajian Sosiologis-Historis - Muzakki, Hawwin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
Islam bring the message as a religion of “rohmatan lil 'alamin”. However, post-prophetic Islam turned into ideological extremism. The author will focus the discussion with the formulation of the problem: How does the process of changing Islam from rohmatan lil 'alamin become an ideology through sociological-historical analysis? How to restore Islam to be a rohmatan lil 'alamin for future Islamic development through sociological-historical analysis? The purpose of this discussion to trace the transformation of Islamic into ideology and explores Islam rahmatan lil alamin in Indonesia, for moderate vision of Islam Nusantara. The author will discuss using the theory of social construction (externalization, objectivity, internalization) by Peter L. Berger. The results revealed that, externally Islam brought by the Prophet Muhammad brought the teaching of rohmatan lil'alamin. The rohmatan lil 'alamin value is objectified by the Arabic characteristic of the ashobiyah. The ashobiyah nature of the Arab nation is internalized into society through ideological extremities. To restore Islam rohmatan lil 'alamin, the writer review Islam Nusantara. Islam is externalized in Indonesia through peaceful way. Islamic teachings finally objectified by the plural Indonesian society and influenced “Ethical Java”. Plural nature and maintain harmony in the ethics of Java is embedded character of moderation values ??(Tawassuth, Tawâzun, I'tidâl, Tasâmuh). This research contributes, to the development of Nusantara Islam which is a model of Islam that is not only centered on Arabia and realize Islam that preach rahmatan lil 'alamin.